Biomotor Analysis in Identifying Talented Athletes Roller Skates Sports: Literature Review of Sports Performance - Sukamdi; M. Yanuar Rizky; Wasis Himawanto (NUSANTARA SPORTA: Jurnal Pendidikan dan Ilmu Keolahragaan, 2023)
This study aims to determine the biomotor factors needed by talented athletes in roller skating and to determine the biomotor components in roller skating. Roller skating is a sport that requires special skills in balance, strength, speed, flexibility, endurance and agility. Identification of talented athletes at an early stage can help to develop potential in athletes. The formulation of the problem in this research is what biomotor factors are needed by talented athletes in roller skating. This study uses the literature review method. The data source used comes from the results of research publications in national and international journals. The process of collecting data using Google Scholar. The journal used was published in full text, with the results obtained that the number of journals was 50 articles fulfilling the inclusion criteria of 6 articles and then analyzed using descriptive quantitative methods. The conclusion of the results of this study is that the 6 articles agree that biomotor factors are needed to identify seed skate athletes with 6 biomotors, namely agility, balance, strength, speed, endurance, flexibility. is that what is needed by biomotor in talented athletes in the field of roller skating is agility, balance, strength, speed, endurance, flexibility. Thus, the identification of talented athletes can be carried out more effectively and efficiently